Production of oogonia and oospores of Leptolegnia chapmanii Seymour (Straminipila: Peronosporomycetes) in Aedes aegypti (L.) larvae at different temperatures - Pelizza, Sebastián Alberto (2010)
The aquatic oomycete fungus Leptolegnia chapmanii Seymour is pathogenic to mosquito larvae, but it has been little studied since it was first isolated. Although studies have been performed on different biological isolates of L. chapmanii around the world, they were made on zoospores and a very little or even nothing is known about the sexual stage (oogonia and oospores), which allows L. chapmanii to remain in the environment when conditions are not favorable. The main objective of this study was to determine the relationship between temperature and time of onset of L. chapmanii oogonia and oospores in Ae. aegypti larvae. Leptolegnia chapmanii-infected IV instar Ae. aegypti larvae were incubated at different temperatures between 5 and 45°C and photoperiod-controlled for 90 days. The number of oogonia and oospores was examined daily for each tested temperature. As was expected, low temperatures extended the times of oogonia formation, as much as seven times. Likewise, temperatures significantly affect the number of oogonia produced.